RANCANG BANGUN SEPEDA LISTRIK UNTUK PENDERITA CACAT KAKI - Eko Sulistyo; Rodika Rodika (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2016)
This time the need of transport's mode for the disabled leg is not maximized. To fulfill these need, we need the necessary transportation tools, one of the tools is a bike. However, the existing bike cannot be used for patients with leg disabilities. The purpose of this research is to design an electric bike wake for the disabled leg with movers using hand paddles and electric system. Bikes are made to be able to provide a low risk of injury while driving and can be used on any terrain. This research will be focused on the design and make electric bike frame for the disabled leg with brushless motor drive and battery charging via PLN's electricity. The stages of the research is the first stage of drafting the bike according to the list of needs. The concept design electric bikes are made with size 1270 x 850 x 1226 mm and uses three wheels. For the movers using brushless DC motors 350 Watt / 48 V with battery accu used 12V / 7 Ah combined series of 4 pieces battery and for manual use paddle power hand. The second stage of is the process of making electric bike. The third stage of is the process of testing an electric bike. Tests performed include testing the strength of the frame, tilt test and movers’s test on the bike. From the results of Static test performed that by loading 70 kg on the bike showed the bike suffered no damage and passed the test. In testing of stability with position of the front wheel facing upwards, downwards and sideways with make a tilt angle of 100. The test results revealed bike was not damaged and will not tip so the bike passed the test. For the test movers electric bike, the speed of electric bicycles from testing up to 20Km / h on a straight road for 1 hour and charging time for 3.5 hours using a charge battery 48V / 2A through voltage PLN’s source. Keywords: Foot deformity, Stability, Electric bikes